New alkaloids from Daphniphyllum himalense. Issue 50 (5th May 2016) - Zhang, Hua; Zhang, Dong-Dong; Li, Jing-Ya; Shyaula, Sajan L.; Li, Jia; Yue, Jian-Min
Abstract : A series of Daphniphyllum alkaloids with selective kinase inhibitory activity were isolated and structurally characterized from Daphniphyllum himalense . Abstract : Nine new Daphniphyllum alkaloids (1–9 ) and 16 biosynthetically related known ones were obtained during the phytochemical investigation into a Nepalese plant, Daphniphyllum himalense . Structures were assigned to these compounds based on careful spectroscopic interpretation and NMR comparison with literature data. Deuteration of H2 -16 in CD3 OD due to quick keto-enol tautomerization was observed for both2 and3 . The recently reported 3β-hydroxydaphniyunnine A was re-examined and its structure was revised to be 21-deoxymacropodumine D via X-ray diffraction analysis. All the isolates were screened preliminarily for their in vitro inhibitory effects against four kinases, PTP1B, aurora A, HDAC6 and IKK-β, and selective alkaloids exhibited weak activities at 20 μg mL −1 .